High surface area mesoporous activated carbon-alginate beads for efficient removal of methylene blue - Nasrullah, A. (Elsevier B.V., 2018)
High surface area mesoporous activated carbon-alginate (AC-alginate) beads were successfully synthesized by entrapping activated carbon powder derived from Mangosteen fruit peel into calcium-alginate beads for methylene blue (MB) removal from aqueous solution. The structure and surface characteristics of AC-alginate beads were analyzed using Fourier transform infra-red (FTIR) spectroscopy, scanning electron microscopy (SEM) and surface area analysis (SBET), while thermal properties were tested using thermogravimetric analysis (TGA). The effect of AC-alginate dose, pH of solution, contact time, initial concentration of MB solution and temperature on MB removal was elucidated. The results showed that the maximum adsorption capacity of 230 mg/g was achieved for 100 mg/L of MB solution at pH 9.5 and temperature 25 Â°C. Furthermore, the adsorption of MB on AC-alginate beads followed well pseudo-second order equation and equilibrium adsorption data were better fitted by the Freundlich isotherm model. The findings reveal the feasibility of AC-alginate beads composite to be used as a potential and low cost adsorbent for removal of cationic dyes. Â© 2017 Elsevier B.V.